Dexrazoxane use in pediatric patients with acute lymphoblastic or myeloid leukemia from 1999 and 2009: Analysis of a national cohort of patients in the pediatric health information systems database1. Issue 4 (4th September 2012) - Walker, Dana M.; Fisher, Brian T.; Seif, Alix E.; Huang, Yuan‐Shung V.; Torp, Kari; Li, Yimei; Aplenc, Richard
Abstract Background Acute lymphoblastic (ALL) and myeloid leukemia (AML) account for approximately 26% of pediatric cancers. Anthracyclines are widely used to treat these leukemias, but dosing is limited by cardiotoxicity. Data support the efficacy of dexrazoxane as a cardioprotectant in children; however, dexrazoxane use in children is not universally accepted due to concerns about toxicity, impact on the antitumor effect of anthracyclines, and risk of secondary malignant neoplasms (SMN). Procedure We conducted a retrospective cohort study to describe patterns of dexrazoxane use in pediatric patients with ALL or AML using the Pediatric Health Information Systems (PHIS) database. Patients identified as having de novo ALL and AML at these PHIS hospitals were included. Results Of 8, 733 patients with ALL and 2, 556 with AML, 207 (2.4%) and 52 (2.0%) received dexrazoxane, respectively. Dexrazoxane use was greater in older children with ALL and AML and in black patients and males with ALL. Dexrazoxane use varied across time and by region in ALL, but not in AML. Prescribing practices differed across institutions and most patients received the first dose early or late after the start of leukemia treatment. Conclusions Dexrazoxane administration is limited in patients with ALL and AML and prescribing practices vary across the country. Further work is necessary to understand how dexrazoxane is used in patients at highest risk of developing cardiotoxicity and to define its true effect on the development of SMNs. Pediatr Blood Cancer 2013; 60: 616–620. © 2012 Wiley Periodicals, Inc.